Analyzing tourist satisfaction towards tour guides performance at Parama Iswari Exhibition - Hossiana Geananda Putri; Sevira G. A. Maturbongs; Yohana Agnescia; Hesti Purwaningrum (Journal of Rural Tourism, 2024)
Purpose - The purpose of this study is to examine how tour guide skills, knowledge, and attitude—through intrapersonal and interpersonal servability—affect tourist satisfaction at the Parama Iswari Exhibition.Methodology/Design/Approach - The study uses a descriptive qualitative approach with data triangulation and focus group discussions. Data were collected through direct observation, interviews, and document studies.Finding - The study found that the tour guides' intrapersonal and interpersonal servability performance positively influenced tourist satisfaction. This highlights the importance of the competency of tour guides, including their skills, knowledge, and attitudes, in enhancing the overall tourist experience.Originality/Value - This research emphasizes the role of tour guides' competencies in influencing tourist satisfaction. It underlines how the tour guide's personal and interpersonal qualities can significantly impact the quality of the tourist experience, offering insights for improving service standards in exhibitions and similar settings.